Symbolic objects and their dual reality. A path towards the symbolic understanding of virtual reality images in childhood - Díaz, Paula (2024)
Based on classical authors and empirical work, this article proposes a discussion about the questions that, due to its specific characteristics, virtual reality raises in the understanding of its images as symbolic objects in early childhood. Symbolic objects are entities that since time immemorial have been created with the intention of representing something other than themselves, which is why they are considered to have a double nature. There are numerous studies regarding the understanding of various symbolic objects, such as models, drawings, maps; also, and more recently, of images embodied in tactile digital technologies such as tablets or smartphones. However, the questions concerning immersive images, as symbols of reality, have not yet been addressed. This paper mainly discusses the question about the symbolic understanding of virtual reality images in early childhood and its possible use in the educational field.